Effect of cement types on the tensile strength of metallic crowns submitted to thermocycling - Consani Simonides; Santos Julie Guzela dos; Correr Sobrinho Lourenço; Sinhoreti Mário Alexandre Coelho; Sousa-Neto Manoel Damião (Fundação Odontológica de Ribeirão Preto, 2003)
The relationship between metallic cast crowns and tensile strength according to cement types submitted to thermocycling was studied. Seventy-two metallic crowns were cast with Verabond II Ni-Cr alloy and cemented in standardized preparations with 10º tapering. Three types of finishing line (45-degree chamfered, 20-degree bevel shoulder and right shoulder) were made with diamond burs on bovine teeth. Twenty-four metallic crowns in each group were randomly subdivided into three subgroups of 8 samples each according to the cement used: SS White zinc phosphate cement, Vitremer resin-modified glass ionomer cement, and Rely X resin cement and were submitted to thermocycling. Retention was evaluated according to tensile load required to displace the metallic cast crowns from tooth preparations with an Instron testing machine. ANOVA and Tukey's test showed a statistically significant difference among luting materials, with greater results for Rely X resin cement (24.9 kgf) followed by SS White zinc phosphate cement (13.3 kgf) and Vitremer resin-modified glass ionomer cement (10.1 kgf). The finishing line types did not influence the tensile resistance of the crowns fixed with the three cements. Increased tensile resistance of metallic crowns fixed on bovine teeth was obtained with resin cement, independent of the finishing line types.